Alternative Material for the plastic injection molding of the Kia Rio's ventilation grille (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
This research was based on the selection of an alternative material for the manufacture by plastic injection of the Kia Rio's ventilation grille. This accessory has a high acquisition cost because the vast majority are imported elements. Therefore, a composite material was sought that can replace the original, which was found in a local environment and is applicable in the plastic injection manufacturing process. The COPRAS multi-criteria method was used to choose the ideal material to replace the original, which was ABS-PC, with PP-20% Bamboo fiber. Finally, once the ideal candidate has been obtained, the next step was to carry out simulations of the plastic injection process with computational fluid dynamics (CFD) analysis software for plastics; these simulations were carried out for the original material. The results obtained by the multicriteria selection criterion showed that PP-20% bamboo fiber is the ideal candidate to replace the original. This result was corroborated by the CFD simulation that demonstrated that it has the best characteristics to be applied in the plastic injection process.